INTERNALISASI AJARAN TRI KAYA PARISUDDHA DALAM MEWUJUDKAN GENERASI UNGGUL DAN BERMARTABAT DI SEKOLAH TINGGI AGAMA HINDU NEGERI MPU KUTURAN SINGARAJA - Putu Sanjaya; Kadek Soni Sumartini (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2022)
The vision of Mpu Kuturan State Hindu High School is Excellence and Dignity with Tri Kaya Parisudha character. As a vision of the institution, all the people in it should understand and implement it in every activity of the institution, both in the academic and non-academic fields. In its implementation it requires the cooperation of all parties, as well as an implementation strategy for the proper internalization of Tri Kaya Parisudha so that the ideals of giving birth to a superior and dignified generation of graduates can be achieved.Keywords: Internalization, Excellence, Dignity, Tri Kaya Parisudha